2022
DOI: 10.1111/nph.18080
|View full text |Cite
|
Sign up to set email alerts
|

Partners to survive: Hoffmannseggia doellii root‐associated microbiome at the Atacama Desert

Abstract: Summary The discovery and characterization of plant species adapted to extreme environmental conditions have become increasingly important. Hoffmannseggia doellii is a perennial herb endemic to the Chilean Atacama Desert that grows in the western Andes between 2800 and 3600 m above sea level. Its growing habitat is characterized by high radiation and low water and nutrient availability. Under these conditions, H. doellii can grow, reproduce, and develop an edible tuberous root. We characterized the H. doelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 113 publications
(157 reference statements)
0
13
0
Order By: Relevance
“…Previous studies on the soil microbiota along this altitudinal gradient have shown that soil fertility is associated with both plant cover and microbial diversity [ 34 , 36 , 60 ]. In addition, plant soil-associated microbiota from the TLT have been characterized to understand the biotic factors that could influence their ability to survive in this harsh environment [ 25 , 26 ]. Knowing that plant‒microbe interactions involve mechanisms by which microbes act beneficially in promoting plant growth, such as nitrogen fixation, protection against pathogens and drought resistance, among others [ 25 , 26 , 35 ], the above works suggest that a modulation of soil microbial diversity may be a characteristic of plants that are highly tolerant to diverse and extreme environments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on the soil microbiota along this altitudinal gradient have shown that soil fertility is associated with both plant cover and microbial diversity [ 34 , 36 , 60 ]. In addition, plant soil-associated microbiota from the TLT have been characterized to understand the biotic factors that could influence their ability to survive in this harsh environment [ 25 , 26 ]. Knowing that plant‒microbe interactions involve mechanisms by which microbes act beneficially in promoting plant growth, such as nitrogen fixation, protection against pathogens and drought resistance, among others [ 25 , 26 , 35 ], the above works suggest that a modulation of soil microbial diversity may be a characteristic of plants that are highly tolerant to diverse and extreme environments.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, at each vegetation belt, seven plant species were sampled to obtain 21 soil samples. For each plant species, the root system was gently shaken to obtain the RSS fraction (~ 100 g, [ 26 ]). BS samples (100 g) were collected in triplicate at 10 cm depth from the ground and at least 1 m away from each sampled plant to obtain 21 soil samples per vegetation belt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the abundance and activity of PGPBs in natural systems have been scarcely explored, despite its great potential and novelty ( Pérez-Jaramillo et al, 2018 ; Leontidou et al, 2020 ). For example, PGPBs associated to wild (or native plants) species have been reported in harsh environments, such as desert ( Fuentes et al, 2020 ; Maldonado et al, 2022 ), alpine ( Sezen et al, 2016 ; Adamczyk et al, 2019 ; Wang et al, 2020 ), and saline environments ( Rueda-Puente et al, 2019 ). Additionally, some studies have explored the presence of PGPBs adapted to environments with extreme conditions, such as salinity, (e.g., PGPBs studied from the soils of Lonar Lake in India, Hingole and Pathak, 2016 ), drought (e.g., PGPBs from different desert regions of Egypt, Ashry et al, 2022 ), or low temperatures (e.g., isolated PGPBs from the Himalayas, Yadav et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…2101(King et al, -2110; (2) use of habitat-adapted microbiomes to promote host tolerance to warming (Carrell et al, 2022(Carrell et al, , in this issue pp. 2111(Carrell et al, -2125; and (3) utilization of microbes from extreme desert environments (Maldonado et al, 2022(Maldonado et al, , in this issue pp. 2126(Maldonado et al, -2139.…”
mentioning
confidence: 99%